Peran Wakaf Tanah Produktif Tehadap Peningkatan Sosio – Ekonomi Masyarakat Islam di Medan Sumatera Utara - Mukhlis Mukhlis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research will provide an overview of the role of productive land waqf on the socio-economic improvement of the Islamic community in Medan, North Sumatra. This research method was carried out with qualitative descriptive research, the research location was carried out in Medan City. The results of this study are the use of productive waqf land is directed to the first three components to people who need funds for daily life, providing a third free education, free health services. part of the economic system that can help lift human goodness and values from underdevelopment. The utilization of the results of productive waqf land management gives a positive impression on the life of the Islamic community in the city of Medan, North Sumatra.